2018
DOI: 10.1111/ap.12353
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Experiences of Culturally and/or Linguistically Diverse Trainee Psychologists in Australian Postgraduate Programs

Abstract: Objective The study explored the experiences of trainee psychologists from a culturally and/or linguistically diverse (CALD) background in Australia. Although previous studies have documented the experiences of CALD trainees in the USA and UK, few studies have explored this issue in Australia. Findings from other countries may aid understanding, but could not be assumed to apply in Australia. The current study aimed to address this gap and explore what facilitated or hindered CALD trainee psychologists’ progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Ng () described how international students might bring different perspectives to counselling—we demonstrated the breadth of placement settings, across multiple areas of psychological practice, and the multiple ways that international psychology students used their intercultural skills to benefit clients and organisations, as well as their peers. Our findings were also similar to those of Ho (), who studied culturally and linguistically diverse (CALD) psychology students on placement. Ho found that CALD students also talked about being mindful and flexible, as well as having specific skills for working with CALD clients.…”
Section: Discussionsupporting
confidence: 89%
“…Ng () described how international students might bring different perspectives to counselling—we demonstrated the breadth of placement settings, across multiple areas of psychological practice, and the multiple ways that international psychology students used their intercultural skills to benefit clients and organisations, as well as their peers. Our findings were also similar to those of Ho (), who studied culturally and linguistically diverse (CALD) psychology students on placement. Ho found that CALD students also talked about being mindful and flexible, as well as having specific skills for working with CALD clients.…”
Section: Discussionsupporting
confidence: 89%
“…Mentor from similar background e.g., employer, higher year level international student Ho & O'Donovan, 2018) Cross-culture mentor program e.g., with domestic non-CALD student (Goodwin & Mbah, 2019;Scherer et al, 2019) Small group support e.g., debriefing/hearing about other CALD students' experiences (Dlamini & Martinovic, 2007;Jackson, 2017) Collaborating learning by having peer interactions e.g., peer placements, peer review of cases, peer interactions in workshops (Dressel et al, 2007) Supportive Supervisor Placement educator Characteristics e.g., approachable (Lalor et al, 2019), encouraging (Brice & Kosta, 1998), patient (Ho & O'Donovan, 2018), motivated (Pitkajarvi, Eriksson, Kekki et al, 2012) and interested in students' lives and backgrounds (Havery, 2019) Learn how to pronounce students' names (Bolderston et al, 2008) Open communication e.g., allow questions, provide clarification (Bolderston et al, 2008) Regular contact with student (Ortlipp & Nuttall, 2011; Advocate for student to where cultural biases occur e.g., system wide or with clients/patients' assumptions (Mori et al, 2009) Time for educator to supervise e.g., reduce workload (Pitkajarvi, Eriksson, Kekki et al, 2012;Spooner-Lane et al, 2009)…”
Section: University/ Workplacementioning
confidence: 99%
“…Normalise and affirm the presence of international students when working with workplaces Screen educators for cultural responsiveness (Ho & O'Donovan, 2018) and allocate to motivated educators (Pitkajarvi et al, 2012) Consider strengths and weaknesses of student (Goodwin & Mbah, 2019;Jackson, 2017;Jones et al, 2017) Student selected placement (Pitkajarvi et al, Cultural mentoring e.g., helping students to understand culture of workplace, clients, other students (Buckworth et al, 2015;Dressel et al, 2007) Be culturally sensitive, culturally aware and consider acculturation affecting performance and learning (Barton et al, 2015;Scherer et al, 2019) Avoid/explain colloquialisms, jargon and culture-based idioms (Bolderston et al, 2008;Hagqvist et al, 2020) Facilitate students interacting with each other on placement (Attrill et al, 2016b;Woodward-Kron et al, 2007…”
Section: Universitymentioning
confidence: 99%